Gene co-expression network and functional module analysis of ovarian cancer. (1st January 2011) - Hong, Shengjun; Dong, Hua; Jin, Li; Xiong, Momiao
We constructed gene co-expression networks and identified the ovarian cancer-related genes by network structure analysis in two independent ovarian cancer studies. To study the properties of networks, modules were identified and their functions and roles were investigated. Our results showed that the inferred networks were structurally conservative and the identified modules were highly overlapped between two data sets. We discovered 42 common hub genes and four common conserved modules, which were enriched with the genes in four cancer-related pathways in two independent studies. In addition, we detected two ovarian cancer susceptibility genes: CCEN2 and BRIC5.